1966
DOI: 10.2307/4592788
|View full text |Cite
|
Sign up to set email alerts
|

California Group Arboviruses in Florida and Report of a New Strain, Keystone Virus: Epidemiologic and Virological Observations in the Tampa Bay Area

Abstract: Epidemiologic studies were directed in part by Dr. Emily H. Gates, biological studies by Dr. Wil¬ liam L. Jennings, entomological identification by Karen Meadows, serologic work by Florence Y. Lewis, and statistical analyses by Ingrid Baughman. all on the staff of the Encephalitis Research Center. Public Health Service research grant A1-05504-02,03 partly supported the studies in Florida. De¬ partment of the Army contract DA-49-193-MD-2042 and Public Health Service research grant Al-02686 partly supported the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…8 In a previous study, osteophytes were found in the lumbar vertebrae of adult boars, but they did not cause vertebral canal stenosis. 3 Vertebral fractures have been associated with lactation osteoporosis, 6 electrocution, 1 and suppurative spondylitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 In a previous study, osteophytes were found in the lumbar vertebrae of adult boars, but they did not cause vertebral canal stenosis. 3 Vertebral fractures have been associated with lactation osteoporosis, 6 electrocution, 1 and suppurative spondylitis.…”
mentioning
confidence: 99%
“…This is the first report of canine LACV infection in the state of Florida, although reports indicate high populations of the vector mosquito in this area. 8,21,32,43,47 LACV is an RNA Bunyavirus, included in the California serogroup that includes snowshoe hare, Jamestowne Canyon, and trivittatus viruses reported to cause human disease in North America. 44 LACV was first isolated in LaCrosse, Wisconsin, in 1964 from the brain of an encephalitic child.…”
mentioning
confidence: 99%
“…New isolates were assigned to existing serological groups or established as groups in themselves when other isolates were shown to be serologically related. Consequently, the CEV prototype isolated in 1943 (Mammon and Reeves 1952) became the nucleus of the California group when later isolates were shown to have a serological affinity to CEV (Mammon and Sather 1966). When Whitman and Shope (1962) found that California group viruses were related to Bunyamwera group viruses, the Bunyamwera supergroup was formed which included a number of smaller groups (World Health Organization 1967).…”
Section: Materials and Methods 17mentioning
confidence: 99%
“…Mammon and Sather (1966) cited an electron microscopy study that reported a virion also in the 50-60 nm size range for CEV.…”
Section: Biochemical and Biophysical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation